Study of Parametric Interactions in the Nuclear Reactor Control with Feedback - V. V. Opiatiuk; I. L. Kozlov; V. I. Skalozubov; I. A. Ostapenko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
This article considers the principal theoretical possibility of regulating a nuclear power reactor under changing operating modes conditions when external periodic disturbances take place in conditions of changing the operating mode. By the external periodic perturbation a downward change in the conditions of the heat sink was meant. The magnitude of the changes was preliminarily calculated in such a way that the operating conditions of the power plant did not exceed the boundaries of the safe operation zone of the reactor. In the case of approaching the operation parameters to the critical ones, the heat sink was increased until the working conditions returned to their previous state. In this work the amplitude frequency response of a non-linearly enhanced system in the nuclear power plant operating conditions when non-linearly reacting to external periodic influences has been studied. The external cyclic disturbances effect produced on the reactor that initially existed under stationary operating conditions has been considered. The research was carried out by numerical simulation of the competition between processes occurring in a nuclear power plant and determined by the system’s reaction time and relaxation time while responding to periodic external influences. Calculations of the relaxation time dependence on the fixed frequency-revealing external influence’s temperature are presented. Also, the relaxation time dependence on the frequency of external influence at a fixed temperature for systems with various relaxation periods was calculated. It is determined that when the dependence between system temperature and the external influence time is calculated, there exists a wide range of possible frequency control. To evaluate the behavior of a nuclear power reactor under conditions of operating modes changes, a fundamental physical mathematical model of the reactor’s state under external harmonic influence is presented. It is based on the nonlinear Riccati equation. The external harmonic effect was simulated by changing the heat supply and heat removal conditions near the critical point.